Effects of long‐term ketamine administration on rat bladder protein levels: A proteomic investigation using two‐dimensional difference gel electrophoresis system. (5th February 2013) - Gu, Di; Huang, Jun; Shan, Zhengfei; Yin, Youle; Zheng, Shaobin; Wu, Peng
Abstract : Objectives: Long‐term ketamine abuse can affect the urinary system, resulting in interstitial cystitis‐like syndrome. However, its pathogenesis remains unclear. In the present study, a proteomic approach of two‐dimensional difference gel electrophoresis followed by matrix‐assisted laser desorption/ionization time‐of‐light mass spectrometry was carried out to investigate the potential disease‐associated proteins in a rat model of ketamine‐associated cystitis. Methods: Rats were randomly assigned to control, normal saline, low dose of ketamine (10 mg/kg) and high‐dose of ketamine (50 mg/kg) groups with six rats in each group. The two experimental groups were given ketamine hydrochloride i.p. daily, whereas the normal saline group rats were treated with saline. After 16 weeks of treatment, all bladders were excised, and samples from normal saline and high dose of ketamine groups were resolved in two‐dimensional difference gel electrophoresis. Differentially expressed spots were excised and identified by matrix‐assisted laser desorption/ionization time‐of‐light mass spectrometry. Phosphoprotein and non‐phosphoprotein purification, histopathology, immunohistochemistry, and western blot were carried out in all groups. Results: Histological study showed hyperplastic epithelium and inflammatory cells infiltration in the high dose of ketamine‐treated rat bladders. Two‐dimensional difference gel electrophoresis revealed 30 altered expressions between the normal saline and high dose of ketamine‐treated group. Among these proteins, two upregulated and two downregulated protein spots were all identified as smooth muscle protein‐22/transgelin. Immunohistochemical staining and western blot analysis showed that the expression of total transgelin had no significant difference between groups. However, the expression of phosphorylated transgelin in the low‐dose and high dose of ketamine groups was increased, whereas the non‐phosphorylated transgelin was decreased when compared with the normal saline group. Conclusions: Long‐term ketamine abuse induces phosphorylation of transgelin in the bladder wall, and this might play an important role in the pathogenesis of ketamine‐associated cystitis.